Identifikasi dan Karakteristik Sarang Penyu di Cagar Alam Mas Popaya Raja | Identification and nest characteristics of sea turtles in Mas Popaya Raja Nature Reserve - Fadjrin Buhang; Abd Hafidz Olii; Sri Nuryatin Hamzah (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2016)
Artikel ini mengidentifikasi jenis penyu dan karakteristik sarang peneluran penyu di Pulau Popaya. Penelitian dilaksanakan pada bulan Februari sampai dengan Oktober 2015 di Kawasan Cagar Alam Mas Popaya Raja Kabupaten Gorontalo Utara. Metode yang digunakan adalah metode survei. Ditemukan 3 (tiga) jenis penyu yaitu Chelonia mydas, Eretmochelis imbricata dan Caretta caretta. Chelonia mydas memiliki sarang peneluran dengan lebar jejak rata–rata 145,3 cm, panjang jejak rata–rata 31 m, kedalaman rata–rata 54,6 cm, diameter rata–rata 23,3 cm x 25,1 cm, suhu rata–rata 30,6°C, sarang terletak pada pantai dengan lebar rata–rata 31,6 m dan sudut kemiringan rata–rata 14,11°. Eretmochelis imbricate memiliki lebar jejak sarang rata–rata 141,2 cm, panjang jejak rata–rata 21,1 m, kedalaman rata–rata 39,6 cm, diameter rata–rata 19,8 cm x 23,1 cm, suhu rata–rata 30,5°C, lebar pantai rata–rata 31,6 m dan sudut kemiringan pantai rata–rata 12,86°. Caretta caretta memiliki lebar jejak sarang± 148 cm panjang jejak ± 32,6 m, kedalaman±44,5 cm, diameter±20 cm x 25 cm, suhu rata– rata 30,3°C, lebar pantai±34 m dan sudut kemiringan pantai ±12,41°. This article identifies species of turtles and the characteristics of turtle nesting holes on Popaya Island. The study was conducted from February to October 2015 in Mas Popaya Raja Nature Reserve, North Gorontalo District. The method used is a survey method. Found 3 (three) types of turtles namely Chelonia mydas, Eretmochelis imbricata and Caretta caretta. Chelonia mydas has nesting holes with an average trail width of 145.3 cm, average trail length of 31 m, average depth of 54.6 cm, average diameter of 23.3 cm x 25.1 cm, average temperature of 30.6 ° C, the nests are located on the beach with an average width of 31.6 m and an average slope angle of 11.11 °. Eretmochelis imbricatehas an average nest trail width of 141.2 cm, average trail length of 21.1 m, average depth of 39.6 cm, average diameter of 19.8 cm x 23.1 cm, average temperature of 30.5 ° C, an average beach width of 31.6 m and an average beach slope of 12.86 °. Caretta caretta has a nest trail width of ± 148 cm trail length ± 32.6 m, depth of ± 44.5 cm, diameter ± 20 cm x 25 cm, average temperature of 30.3 ° C, average beach width of 34 m and average slope angle beach of 12.41 °. Katakunci: penyu; identifikasi; sarang; cagar alam. Keywords: sea turtle; identification; nest; nature reserve.